Primary Intradural Extramedullary Extra-OsseousEwing’s Sarcoma of Cervical Spine (C5-C7): A Case Report and Review of Literature - Gubbala, Srinivas DD; Mattaparti, Sridevi; ., Bhavani (Annals of Pathology and Laboratory Medicine, 2019)
Ewing's sarcoma is a rare aggressive tumor common in bone or skeletal component. Primary Intradural Extra-medullary Extra-Osseous Ewing sarcoma of cervical spine is extremely rare malignant neoplasm and only few cases have been reported in the literature. There is a paucity of data regarding the clinical features, natural course, pre-operative diagnosis, treatment modalities and post-operative management. Herein, we report a case of a 22-year-old man who presented with inability to walk and numbness in both lower limbs. MRI findings suggested a possibility of nerve sheath tumor but was diagnosed as Intradural Extra-skeletal Ewing sarcoma on histopathological analysis. The literature with regard to primary spinal intradural extra-skeletal Ewing sarcoma was reviewed.